PEREMPUAN TANPA ANAK: STRATEGI MENGHADAPI STIGMA - Priandono, Tito Edy; Ramdani, Alwan Husni; Affandi, Ahmad Fahrul Muchtar (Jurnal Common, 2022)
Research related to the stigma of women without children is still rarely studied, especially in Indonesia. The problem of childless women is a latent phenomenon. In some developed countries, childless women experience the psychological impact of the stigma they receive. Based on these factors, the researcher wants to examine two important aspects, namely how to experience the stigma faced by women without children. Second, how women without children manage the stigma they face. Researchers use the Stigma Management Communication theory approach to dissect the problem. This study used qualitative data by conducting interviews with 9 women who experienced childless conditions for at least 3 years since marriage. The results showed that informants experienced labeling as workaholic women, especially from the family environment. The informants used two strategies, namely accepting stigma and opposing stigma. The impact felt by informants after receiving the stigma was that they were optimistic, felt lonely, and lived a more peaceful life. Meanwhile, informants who oppose stigma have the effect of increasing self-confidence and focusing more on personal life. Researchers recommend that in the future there will be research related to ethnic culture.